Modelling the effects of self-regulation, perceived usefulness, confirmation and satisfaction on the continuous intention to utilise mobile learning applications - Alshammari, Sultan Hammad; Alkhabra, Saleh (Frontiers in Education, 2025)
Although m-learning applications have been widely used in universities, the factors that might affect the continuous intention to utilise them have not been fully addressed. Therefore, this study aimed to understand this by extending the expectation confirmation model (ECM) and incorporating self-regulated learning (SRL). A quantitative research design was adopted, and data were gathered using a structured questionnaire distributed to 227 undergraduate university students through simple random sampling. The data were analysed using structural equation modelling (SEM) in AMOS. The findings revealed that the proposed model has high explanatory power (79%), which explains the phenomena of influential factors. Additionally, students’ perceived usefulness (PU) and satisfaction had a positive direct significant effect on students’ continuous intention to use m-learning applications. However, perceived usefulness did not affect satisfaction but confirmation did. Furthermore, SRL had an indirect positive effect on continuous intention, while it had a direct significant effect on both perceived usefulness and confirmation. The practical and theoretical implications of this study are further discussed in detail.